Peran Guru PAI HONORER dalam Proses Pembelajaran pada MAN 1 SIMEULUE - Miswar Miswar (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2022)
Teachers have an important role in the learning process, because the success of learning objectives is largely determined by the teacher's ability to teach. Therefore, teachers must carry out their duties and functions well and correctly. In the learning process, the role of teachers is very necessary, both teachers who are civil servants and teachers who still have honorary status. In this case the author examines the role of honorary PAI teachers in the learning process at MAN 1 Simeulue. What we want to research is the role and professionalism of honorary PAI teachers in the learning process at MAN 1 Simeulue. This research aims to determine the role and professionalism of honorary PAI teachers in implementing learning at MAN 1 Simeulue. This research uses a descriptive analysis method, field research in nature, with data collection techniques through observation, documentation and interviews with respondents who have been selected as samples. Honorary PAI teachers have an important role in learning at MAN 1 Simeulue. The role of the teacher is not only as a teacher, but also as an educator. Teachers also play a role in guiding students to be motivated to learn. The performance of the honorary PAI teachers at MAN 1 Simeulue is professional in carrying out their duties, because the honorary teachers have carried out their duties well in accordance with their fields and expertise. In carrying out their duties, honorary PAI teachers can master teaching materials, are able to manage the class well, are able to interact with students well, are able to use varied methods and are able to use learning media that are appropriate to the teaching material. As educators, honorary PAI teachers at MAN 1 Simeulue carry out their duties because of their calling, moral responsibility, social responsibility and scientific responsibility. Honorary PAI teachers at MAN 1 Simeulue sometimes prioritize this calling and responsibility over the salary/wages they receive. Although in fact they also have the right to get a decent living and respect for working as educators. Honorary teachers also come in on time, teach mandatory hours with full responsibility, guide students inside and outside the classroom and carry out the learning process with full responsibility